Haiti: The security situation of a country deprived of its future - Balogh, Áron (POLARITIES, 2023)
The primary aim of this study is to provide a comprehensive picture of the current security situation of the traditionally under-researched Haiti. The analysis will first describe the main chapters of the state's 200-year history and their impact on our present. The second part will focus on the events of the 2020s, through which I have sought to present a complex security picture. The situation of the Central American state, defined as fragile, may also be relevant for us, as it reminds us that we need to address the issue of stable statehood also in the wider transatlantic area. On the other hand, the security challenges – such as immigration or organized crime – in the neighbourhood of the United States, which is one of the poles of the emerging global world order, deserve increasing attention.